The Potential for Development of the Aua Sarumpun Tourist Attraction - Eka Saputra; Zainal Fadri; Sara Stevenson; Ismail Abdurrahman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The type of research used is descriptive research with qualitative data. This research was conducted using interview instruments, documentation using mobile media, books and pens. In this study, the data sources obtained were primary data sources, namely data found directly in the field and supplemented with secondary data. Meanwhile, the data analysis technique used was data reduction, presentation and drawing conclusions and to check the validity of the data, the researchers used source triangulation, technical triangulation and time triangulation. Based on the research that the authors conducted at the Aua Sarumpun tourist attraction, it was found that there are three potentials that need to be developed at the Aua Sarumpun tourist attraction, namely the potential for human resource development, natural resource potential and cultural potential. The results of this study found that the potential for human resource development in developing the Aua Sarumpun tourist attraction is by building access roads and managing governance at the Aua Sarumpun tourist attraction, while the natural potential is in the form of potential natural resources that exist for the development of the Aua Sarumpun tourist attraction. This Sarumpun is the potential for nature in Aua Sarumpun which still needs a lot to be developed, for example savanna grasslands, good views and a beautiful atmosphere, while for its cultural potential in the form of traditions held at Aua Sarumpun tourist objects in the form of mangroves, eating bajamba , randai, salawat dulang, traditional speeches, chaotic lawuak cooking competitions which are still being displayed at one village event at this Aua Sarumpun tourist attraction.